Clean coal engineering technology - Miller, Bruce G. (Butterworth-Heinemann, 2017)
Clean Coal Engineering Technology, Second Edition provides significant information on the major power generation technologies that aim to utilize coal more efficiently, and with less environmental impact. With increased coal combustion comes heightened concerns about coal’s impacts on human health and climate change, so the book addresses the reduction of both carbon footprints and emissions of pollutants, such as particulate matter, nitrogen oxides, and mercury. Part 1 provides an essential grounding in the history of coal use alongside coal chemical and physical characteristics, worldwide distribution, and health and environmental impacts. Part 2 introduces the fundamentals of the major coal utilization technologies and examines the anatomy of a coal-fired power plant before going on to provide an overview of clean coal technologies for advanced power generation. Next, users will find a group of chapters on emissions and carbon management that have been extensively enlarged and updated for the second edition, thus reflecting the ever-increasing importance of this area. The final section of the book focuses on clean coal technology programs around the world and the future role of coal in the energy mix. This fully revised and selectively expanded new edition is a valuable resource for professionals, including environmental, chemical, and mechanical engineers who seek an authoritative and thorough one-volume overview of the latest advances in cleaner power production from coal.